Perkembangan Intelektual Siswa-siswa SMP - Moh. Amien (Universitas Negeri Malang, 2016)
The study is aimed at finding out students' thinking processes, differences in the students' cognitive development, and differences in the students' cognitive patterns in relation to the teachers' and parents' settings. The population includes SMP students in Yogyakarta. A sample of 1069 students is taken randomly from each class. A multiple choice test of Piaget's cognitive development is given to the sample. Split-half technique of internal consistency is used to estimate the test reliability. Research findings indicate that older students have higher cognitive development than those in rural areas, male students have higher cognitive development than female ones, and students whose parents are more educated have higher cognitive development. One of the implications is that teachers' and parents' encouragement help improve students' cognitive development. Students, especially in the rural areas, therefore, need encouragement to improve their cognitive development